2020
DOI: 10.1002/cncr.33147
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chronic medication adherence, costs, and health care use after a cancer diagnosis among low‐income patients and the role of patient‐centered medical homes

Abstract: BACKGROUND: Approximately 40% of patients with cancer also have another chronic medical condition. Patient-centered medical homes (PCMHs) have improved outcomes among patients with multiple chronic comorbidities. The authors first evaluated the impact of a cancer diagnosis on chronic medication adherence among patients with Medicaid coverage and, second, whether PCMHs influenced outcomes among patients with cancer. METHODS: Using linked 2004 to 2010 North Carolina cancer registry and claims data, the authors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This calls for better communication and coordination between specialists and general practitioners to ensure continuity of care of cancer survivors with DM. Cancer and its treatments may distract individuals with preexisting DM from routine DM management (e.g., poorer adherence to DM medication) 38–40 . As such, keeping a continuous satisfactory DM and hyperglycemia management is essential during long‐term cancer survivorship, and diabetic cancer survivors could benefit from good medication adherence for DM 41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This calls for better communication and coordination between specialists and general practitioners to ensure continuity of care of cancer survivors with DM. Cancer and its treatments may distract individuals with preexisting DM from routine DM management (e.g., poorer adherence to DM medication) 38–40 . As such, keeping a continuous satisfactory DM and hyperglycemia management is essential during long‐term cancer survivorship, and diabetic cancer survivors could benefit from good medication adherence for DM 41 …”
Section: Discussionmentioning
confidence: 99%
“…Cancer and its treatments may distract individuals with preexisting DM from routine DM management (e.g., poorer adherence to DM medication). [38][39][40] As such, keeping a continuous satisfactory DM and hyperglycemia management is essential during long-term cancer survivorship, and diabetic cancer survivors could benefit from good medication adherence for DM. 41 Contrary to previous studies that reported that the prevalence of DM and the risk of new-onset DM in cancer survivors increased with cancer stage and cancer treatment, 3,13,42 our study revealed that cancer stage and cancer treatment were not significantly associated with DM prevalence and incidence in LTCS.…”
Section: Caesar Baselinementioning
confidence: 99%
“…The PCMH model has the potential to reduce racial disparities, but additional unique protocols that address minority populations' needs are necessary. Spees et al (2020) found that PCMHs were associated with improved expenditures and fewer emergency department visits among some low-income cancer patients. However Reddy et al (2015) studied 56 Veterans Health Administration primary care sites using the 5 domains of patient care experience from the Survey of Healthcare Experiences of Patients and did not find an improvement in patient experience among sites that were PCMHs.…”
Section: Aco/pcmh Models Show Inconsistent Data Regarding Patient Exp...mentioning
confidence: 96%